High-thermal-conductivity phase change thermal interface material and preparation method thereof

By using flexible epoxy resin and expanded graphite in a highly thermally conductive phase change thermal interface material, the problem of leakage during application is solved, and the combination of high thermal conductivity and high latent heat of phase change is achieved. Effectively inhibits the leakage of paraffin.

CN119463512APending Publication Date: 2025-02-18CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411616930.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Highly thermally conductive phase-change thermal interface materials are prone to leakage during application, resulting in contamination and damage to electronic devices. It is difficult for the prior art to maintain high phase-change latent heat, excellent thermal conductivity and low leakage rate at the same time.

Method used

Flexible epoxy resin is used as the matrix, combining expanded graphite and phase change particles, and phase change particles are prepared by high-temperature melt blending and pulverization screening, and a highly thermally conductive phase change heat interface material is prepared by vacuum defoaming and cooling.

Benefits of technology

The combination of high thermal conductivity and high phase change latent heat is achieved, while effectively inhibiting the leakage of paraffin and improving the stability and service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463512A_ABST
    Figure CN119463512A_ABST
Patent Text Reader

Abstract

The invention provides a high-thermal-conductivity phase change thermal interface material and a preparation method thereof, and belongs to the field of phase change thermal interface materials, the high-thermal-conductivity phase change thermal interface material comprises the following raw materials by mass: 11.4 parts of epoxy resin, 19 parts of a curing agent, 7.6 parts of dioctyl terephthalate, 59.5-62 parts of phase change particles, and 0-2.5 parts of expanded graphite. According to the high-thermal-conductivity phase change thermal interface material, the phase change particles and the expanded graphite are completely wrapped in the flexible epoxy resin, so that the flexible epoxy resin is endowed with relatively high phase change latent heat and excellent thermal conductivity, and meanwhile, leakage of the phase change material can be effectively inhibited. The preparation technology is simple, the preparation cost is low, good economical efficiency is achieved, and the preparation method is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of phase change thermal interface materials, and relates to a high thermal conductivity phase change thermal interface material and a preparation method thereof. Background Art

[0002] The rapid development of 5G communication technology has put forward higher requirements on the performance and integration of electronic devices, which has significantly increased the risk of overheating of electronic devices. Studies have shown that for every 10 degrees Celsius increase in the operating temperature of electronic devices, their operating reliability will decrease by 50%, and thermal interface materials are like a "thermal bridge" that can transfer the heat of electronic devices to the heat sink faster and then dissipate it.

[0003] Phase change thermal interface materials, as a new type of thermal interface materials, have greatly improved heat transfer efficiency and reliability compared to traditional thermal interface materials. Traditional thermal interfaces (thermal grease and thermal gaskets) mainly improve the heat dissipation efficiency by improving the thermal conductivity of the material itself, while high thermal conductivity phase change thermal interface materials will undergo phase change on this basis, which can not only absorb a large amount of heat, but also further reduce the heat transfer thermal resistance between the thermal interface material and the contact surface, and can significantly enhance the heat dissipation efficiency. From a reliability perspective, thermal grease is easy to dry up and flow, resulting in reduced heat dissipation, and thermal gaskets may be over-compressed and deformed under pressure, while high thermal conductivity phase change thermal interface materials have good shape stability, can adaptively fill gaps after phase change, and can maintain stable heat dissipation efficiency even after long-term use, which can improve the reliability and service life of the entire heat dissipation system.

[0004] In summary, although high thermal conductivity phase change thermal interface materials have many advantages, due to the phase change characteristics of the phase change materials themselves, it is very easy to cause leakage during application, thereby contaminating or even damaging electronic devices. Therefore, we are currently focusing on ensuring that the phase change thermal interface materials have high phase change latent heat and excellent thermal conductivity while maintaining a low level of leakage rate. Summary of the invention

[0005] In view of the above problems, the present invention provides a high thermal conductivity phase change thermal interface material and a preparation method thereof. The thermal interface material uses flexible epoxy resin as a matrix and expanded graphite and phase change particles as fillers, giving the thermal interface material excellent thermal conductivity and phase change latent heat level.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] The present invention provides a high thermal conductivity phase change thermal interface material and a preparation method thereof, comprising the following raw materials in parts by mass: 11.4 parts of epoxy resin, 19 parts of curing agent, 7.6 parts of dioctyl terephthalate, 59.5-62 parts of phase change particles, and 0-2.5 parts of expanded graphite. 11.4 parts of the epoxy resin, 19 parts of curing agent and 7.6 parts of dioctyl terephthalate are weighed and added into a glass beaker, and fully stirred by a high-speed stirrer, and 59.2-62 parts of the phase change particles and 0-2.5 parts of expanded graphite are weighed and added into the glass beaker, and the stirring time is not less than 20 minutes, so that the mixed material has significant phase change latent heat and excellent thermal conductivity, and finally vacuum degassing and cooling to room temperature are performed to prepare the high thermal conductivity phase change thermal interface material.

[0008] Preferably, the dioctyl terephthalate has an ester content of ≥99.5%, a density (25° C.) of 0.982 to 0.988 g / m 3 , and a heating loss of ≤0.3%.

[0009] Preferably, the viscosity of the epoxy resin is preferably 300-500 cst, and the viscosity of the curing agent is preferably 200-300 cst.

[0010] Preferably, the phase change particles are prepared by high temperature melting and blending expanded graphite and paraffin wax in a ratio of 1:20 by mass to form a composite phase change material block. Further, a high-speed pulverizer is used to pulverize the composite phase change material block, and the particles are screened to finally obtain the phase change particles with a particle size of 0.2 to 0.45 mm and less than 0.1 mm.

[0011] Preferably, the latent heat of the paraffin is 220-240 kJ / kg, and the specific heat capacity is 3.22 kJ / (kg·°C).

[0012] The present invention provides a high thermal conductivity phase change thermal interface material and a preparation method thereof, comprising:

[0013] (1) Paraffin is heated at 70° C. until it is completely melted, and expanded graphite is further added to the molten paraffin, and stirred at a speed of 400 r / min for 3 hours to prepare a composite phase change material block. Further, the composite phase change material block is crushed using a high-speed crusher, and particles are screened to finally obtain the phase change particles with a particle size of 0.2 to 0.45 mm and less than 0.1 mm.

[0014] (2) Weigh 11.4 parts of epoxy resin, 19 parts of curing agent and 7.6 parts of dioctyl terephthalate into a glass beaker and stir at 400 r / min for 10 min.

[0015] (3) adding the phase change particles of different particle sizes and expanded graphite obtained in step (1) into the glass beaker, wherein the phase change particles include 35.7 to 37.2 parts of 0.2 to 0.45 mm and 23.8 to 24.8 parts of phase change particles smaller than 0.1 mm, and 0 to 2.5 parts of expanded graphite, and stirring at a speed of 1000 r / min for 20 min.

[0016] (4) Using a vacuum drying oven to perform vacuum degassing and accelerated curing on the prepared mixture material, ultimately obtaining a high thermal conductivity phase change thermal interface material.

[0017] A third aspect of the present invention provides a high thermal conductivity phase change thermal interface material and a preparation method thereof. The thermal interface material is prepared by the above preparation method.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The present invention uses expanded graphite to adsorb paraffin to prepare phase change particles, and then wraps the phase change particles and expanded graphite with a flexible epoxy resin, thereby improving the thermal conductivity of the phase change thermal interface material, giving the phase change thermal interface material a higher phase change latent heat value, and effectively inhibiting the leakage of paraffin.

[0020] (2) The present invention uses a flexible epoxy resin as a matrix. After multiple working cycles, there will be no warping and it can fully and tightly fit the contact surface. When the local temperature of the electronic device gradually rises, the paraffin will change from solid to liquid, which can further reduce the heat transfer resistance. Long-term use can also maintain stable heat dissipation efficiency, which can improve the reliability and service life of the entire heat dissipation system.

[0021] The high thermal conductivity phase change thermal interface material and the preparation method thereof provided by the present invention have simple preparation process and low preparation cost, have good economy, and are suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a graph showing the thermal conductivity test results of Examples 1 to 4 of the present invention and Comparative Example 1;

[0023] Figure 2 1 is a graph showing the phase change latent heat test results of Examples 1 to 4 of the present invention. DETAILED DESCRIPTION

[0024] The purpose of the present invention is to provide a high thermal conductivity phase change thermal interface material and a preparation method thereof, so as to prepare a phase change thermal interface material which has high phase change latent heat, good thermal conductivity and can effectively prevent and control the leakage of phase change materials.

[0025] The invention provides a high thermal conductivity phase change thermal interface material and a preparation method thereof, comprising various component raw materials in parts by mass: 11.4 parts of epoxy resin, 19 parts of curing agent, 7.6 parts of dioctyl terephthalate, 59.5-62 parts of phase change particles, and 0-2.5 parts of expanded graphite.

[0026] The specific embodiments of the present invention will be further explained below with reference to the accompanying drawings and examples.

[0027] The "parts" described in the following examples are all "parts by mass".

[0028] Comparative Example 1

[0029] (A) 11.4 parts of epoxy resin, 19 parts of curing agent and 7.6 parts of dioctyl terephthalate were weighed and added into a glass beaker, and stirred at a speed of 400 r / min for 10 min.

[0030] (B) The prepared mixture material was subjected to vacuum degassing and accelerated curing treatment for 24 hours in a vacuum drying oven at a temperature of 25° C. and a vacuum degree of 5 kPa.

[0031] Example 1

[0032] (A) 200 parts of paraffin wax were heated to completely melt at 70°C, 10 parts of expanded graphite were heated into the molten paraffin wax, and stirred at a speed of 400 r / min for 3 hours to prepare a composite phase change material block. Furthermore, the composite phase change material block was crushed using a high-speed crusher, and the particles were screened to finally obtain phase change particles with a particle size of 0.2 to 0.45 mm and less than 0.1 mm.

[0033] (B) 11.4 parts of epoxy resin, 19 parts of curing agent and 7.6 parts of dioctyl terephthalate were weighed and added into a glass beaker, and stirred at a speed of 400 r / min for 10 min.

[0034] (C) adding the phase change particles of different particle sizes obtained in step (A) and expanded graphite into a glass beaker, wherein the phase change particles include 37.2 parts of 0.2-0.45 mm and 24.8 parts of phase change particles less than 0.1 mm, and 0 parts of expanded graphite, and stirring at a speed of 1000 r / min for 20 min.

[0035] (D) The prepared mixture material was subjected to vacuum degassing and accelerated curing treatment for 24 hours in a vacuum drying oven at a temperature of 25° C. and a vacuum degree of 5 kPa, thereby finally obtaining a phase change thermal interface material with high thermal conductivity.

[0036] Example 2

[0037] The operation is basically the same as that of Implementation Example 1, except that the proportions of phase change particles and expanded graphite are changed to 36.9 parts of 0.2-0.45 mm and 24.6 parts of phase change particles smaller than 0.1 mm, and 0.5 parts of expanded graphite.

[0038] Example 3

[0039] The operation is basically the same as that of Implementation Example 1, except that the proportions of phase change particles and expanded graphite are changed to 36.3 parts of 0.2-0.45 mm and 24.2 parts of phase change particles smaller than 0.1 mm, and 1.5 parts of expanded graphite.

[0040] Example 4

[0041] The operation is basically the same as that of Implementation Example 1, except that the proportions of phase change particles and expanded graphite are changed to 35.7 parts of 0.2-0.45 mm and 23.8 parts of phase change particles smaller than 0.1 mm, and 2.5 parts of expanded graphite.

[0042] The thermal conductivity of the materials of Comparative Example 1 and Examples 1 to 4 was tested using a thermal constant coefficient analyzer (TPS2500S). The test results are as follows: Figure 1 The test results are summarized in the following table:

[0043] Thermal conductivity (W / m·K) Comparison 1 0.18 Example 1 0.66 Example 2 0.82 Example 3 1.12 Example 4 1.4

[0044] The sample with an initial mass of M0 is placed on filter paper in a constant temperature and humidity chamber maintained at 40°C. The sample is taken out and weighed every hour. The mass of the sample after heating in the constant temperature and humidity chamber for n hours is defined as M n , the material leakage rate calculation formula is as follows:

[0045] S=(M0-M n ) / M0×100%

[0046] The final leakage rates of Experimental Examples 1 and 4 after heating for 200 hours were 28.9% and 16.6%, respectively.

[0047] The melting temperature and melting latent heat of the samples were measured by differential scanning calorimetry (DSC-60plus) in a test temperature range of 0-60°C and a heating rate of 5°C / min.

[0048] According to the above method, the test results of Examples 1 to 4 are as follows: Figure 2 As shown, the latent heat value and phase change temperature test results of the obtained material are shown in the following table:

[0049]

Claims

1. A high thermal conductivity phase change thermal interface material and a preparation method thereof, characterized in that: The invention comprises the following raw materials in parts by mass: 11.4 parts of epoxy resin, 19 parts of curing agent, 7.6 parts of dioctyl terephthalate, 59.5-62 parts of phase change particles, and 0-2.5 parts of expanded graphite. The epoxy resin, curing agent and dioctyl terephthalate in parts by mass are weighed and added into a glass beaker, and fully stirred by a high-speed stirrer. The phase change particles and expanded graphite in parts by mass are further weighed and added into the glass beaker, and the stirring time is not less than 20 minutes, so that the mixture of the epoxy resin, curing agent, dioctyl terephthalate, phase change particles and expanded graphite has the functions of phase change heat absorption and heat conduction. Finally, the high thermal conductivity phase change thermal interface material is prepared through vacuum degassing and cooling to room temperature.

2. A high thermal conductivity phase change thermal interface material and a preparation method thereof according to claim 1, characterized in that: The dioctyl terephthalate has an ester content of ≥99.5%, a density (25°C) of 0.982-0.988 g / m3, and a heating loss of ≤0.3%.

3. A high thermal conductivity phase change thermal interface material and a preparation method thereof according to claim 1, characterized in that: The viscosity of the epoxy resin is 300-500 cst, and the viscosity of the curing agent is 200-300 cst.

4. A high thermal conductivity phase change thermal interface material and a preparation method thereof according to claim 1, characterized in that: The phase change particles are prepared by high-temperature melt blending of expanded graphite and paraffin in a ratio of 1:20 by mass to form a composite phase change material block. Secondly, a high-speed crusher is used to crush the composite phase change material block, and particles are screened to finally obtain the phase change particles with a particle size of 0.2 to 0.45 mm and less than 0.1 mm.

5. A high thermal conductivity phase change thermal interface material and a preparation method thereof according to claim 4, characterized in that: The latent heat of the paraffin is 220-240 kJ / kg, and the specific heat capacity is 3.22 kJ / (kg·℃).

6. A high thermal conductivity phase change thermal interface material and a preparation method thereof according to claim 1, characterized in that: The steps include: (S1) heating paraffin at 70° C. until it is completely melted, further adding expanded graphite to the molten paraffin, and stirring at a speed of 400 r / min for 3 hours to prepare a composite phase change material block; secondly, using a high-speed crusher to crush the composite phase change material block, and performing particle screening to finally obtain the phase change particles with a particle size of 0.2 to 0.45 mm and less than 0.1 mm. (S2) 11.4 parts of epoxy resin, 19 parts of curing agent and 7.6 parts of dioctyl terephthalate were weighed and added into a glass beaker, and stirred at a speed of 400 r / min for 10 min. (S3) adding the phase change particles of different particle sizes and expanded graphite obtained in step (S1) into a glass beaker, wherein the phase change particles include 25.7 to 35.2 parts of 0.2 to 0.45 mm and 23.8 to 24.8 parts of phase change particles less than 0.1 mm, and 0 to 2.5 parts of expanded graphite, and stirring at a speed of 1000 r / min for 20 min. (S4) Using a vacuum drying oven to perform vacuum degassing and accelerated curing on the prepared mixture material, and finally obtaining a high thermal conductivity phase change thermal interface material.

Citation Information

Cited By

  • Bio-based recoverable high-thermal-conductivity dynamic ordered network composite material and preparation method thereof

    CN121851328A